PERAN DAN TANTANGAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBANGUN NILAI-NILAI RELIGIUS PESERTA DIDIK PASCA PANDEMI COVID 19 (STUDI KASUS DI SDN SINDANGGALIH KOTA TASIKMALAYA) - Ratno, Dedi (Program Pascasarjana Institut Agama Islam Tasikmalaya, 2023)
The purpose of this study was to determine how the implementation of post-pandemic PAI learning, how the role of PAI teachers in fostering students' religious values, This research uses a qualitative approach using an analytical descriptive method. Data collection techniques used in this research are in-depth interviews, observation and documentation. While the data analysis technique uses the interactive analysis method from Miles and Huberman which consists of three components, namely data reduction, data presentation and verification / conclusion. The results of this study are: 1) The implementation of PAI learning after the co-19 pandemic at SDN Sindanggalih Tasikmalaya City is using three activities in it, namely: a) Initial activities, namely preparing students physically and psychologically, motivating and asking questions about the previous material by linking it to the material to be discussed, conveying the learning objectives to be achieved. b) Core activities, namely delivering material with methods and media that have been prepared, giving assignments and reinforcements to students. c) Final activities, namely giving conclusions, evaluating students on the material that has been delivered and conveying material that will be discussed at the next meeting. 2) The role of PAI teachers in fostering students' religious values is: a) As an educator, b) As a teacher, c) As a mentor, d) As a motivator, e) As an example, f) As an evaluator. 3) The challenges of Islamic Religious Education Teachers in fostering students' religious values at SDN Sindanggalih Tasikmalaya City after the Covid 19 pandemic are: a) Lack of interaction between teachers and students during face-to-face learning. b) Students' learning motivation is still decreasing due to online self-study at home. c) During the learning process, students do not concentrate so that participation and feedback or responses are not created in the learning process. d) Poor student character. e) The culture of religious habituation instilled by the school has faded a little, students forget about this culture and are ignorant in the school environment.